The Composition of Circulating Leukocytes Varies With Age and Melanoma Onset in the MeLiM Pig Biomedical Model - Blanc, Fany; Prévost-Blondel, Armelle; Piton, Guillaume; Bouguyon, Edwige; Leplat, Jean-Jacques; Andréoletti, Fabrice; Egidy, Giorgia; Bourneuf, Emmanuelle; Bertho, Nicolas; Vincent-Naulleau, Silvia (Frontiers in Immunology, 2020)
Immunological research in pigs benefits from many improvements with a direct impact on the veterinary control of pig husbandry and on biomedical models. We compiled the available knowledge to develop gating strategies to monitor simultaneously all blood immune cell types by multicolor flow cytometry in Melanoblastoma-bearing Libechov Minipigs (MeLiM). The MeLiM pig spontaneously develops cutaneous melanomas that regress few months later. We monitored lymphoid and myeloid cell subsets in 3 to 21 week-old pigs. Interestingly, neutrophils, type III monocytes (CD163+ CD14+ MHC II-) and CD4- CD8α- T cells are less abundant in oldest animals in contrast to eosinophils, type II monocytes (CD163- CD14low MHC II+), B cells, γδ T cells, CD4+ CD8α+ and CD4- CD8α+ T cells. Melanoma occurrence led to changes in the blood cell composition. Higher proportions of NK cells, CD4+ and CD4+ CD8α+ T cells and CD21- B cells among B cells are found in young melanoma-bearing piglets, consistent with the immune-mediated spontaneous regression in the MeLiM model.